(untitled) (World Bulletin of Public Health, 2023)
This article contains information about biochemical indicators of liver function in alcoholic and viral hepatitis, as well as markers of viral hepatitis. According to the World Health Organization, about 2 billion people in the world consume alcoholic beverages. Therefore, it is important to distinguish alcoholic hepatitis from viral hepatitis. Undoubtedly, many patients who consume a large amount of alcohol and are even addicted to alcohol can have a high level of aminotransferase in the blood, and at the same time, the ratio of AST / ALT can be normal. To test our hypothesis, we studied the de Ritis coefficient and some laboratory parameters in study participants with alcoholic hepatitis and viral hepatitis B and C.